Representations of Disability in the Old Testament and Their Implication for the Nexus between Poverty and Disability: Lessons for the Church in Contemporary Zimbabwe - Bowa, Makomborero Allen (Old Testament Essays, 2023)
Historically, disability has been part of the human condition such that persons with disabilities have existed in virtually all societies from ancient to modern times. At the core of the experiences of persons with disabilities are contradictory perspectives which have essentially served as inclusion and exclusion mechanisms in the context of disability. The Old Testament (OT) presents such contradictory perspectives on disability in texts that discriminate against persons with disabilities (Lev 21:16–24; 22:17–22; Deut 28:28) as well as texts that call for non-discrimination (Lev 19:14; Deuteronomy 27:18). Accordingly, the negative and discriminatory perspectives on disability that provide the foundation for the systematic exclusion stigmatisation of and discrimination against persons with disabilities in African societies are partly rooted in the Church’s engagement with biblical texts on disability. Such exclusion is the primary mechanism that nurtures and perpetuates the connection between disability and poverty. Drawing insights from the Social Model of Disability, the chapter argues that there has to be a paradigm shift in the way that society has addressed the issue of disability. The Church should take appropriate action to guard against the systematic exclusion of persons with disabilities through a liberative reading of biblical texts that cultivate a social ideology of inclusion in the context of disability. https://doi.org/10.17159/2312-3621/2022/v35n3a3